ANALISIS ASUHAN KEPERAWATAN DENGANINTERVENSI INOVASI VIRTUAL REALITY UNTUKMENURUNKAN SKALA NYERI PADA PASIEN DI IGD RSUD TARAKAN - Nur Rohmah (2023)
Pain is an unpleasant condition that is subjective, this is because the experience or feeling of pain for each individual differs in intensity, quality, duration, and distribution of pain and only that individual can describe and evaluate the pain he or she is experiencing. Pain is one of the most common reasons why patients go to the ER. One of the nursing actions in reducing the pain scale in the emergency room is virtual reality therapy. This study aims to determine the effectiveness of virtual reality therapy to reduce pain scale. The number of respondents in this study amounted to 2 respondents with one person being given the intervention and the other person not being given the intervention. The tool used to assess the pain scale in patients with complaints of pain is measured by the numerical pain scale (NRS 0-10). The results of the analysis of this study were that there was a significant reduction in the pain scale numerical critical scale (NRS 0-10) before and after the intervention was given. Based on this, it can be concluded that virtual reality innovation interventions can reduce the pain scale in patients in the emergency room.